PK/PD Analysis of Marbofloxacin by Monte Carlo Simulation against Mycoplasma agalactiae in Plasma and Milk of Lactating Goats after IV, SC and SC-Long Acting Formulations Administration - Fernández-Varón, Emilio (Animals (Basel), 2021)
SIMPLE SUMMARY: In some countries like Spain and France, contagious agalactia (CA) is a highly relevant issue. CA is a mycoplasmosis affecting small ruminants and it is associated with a relevant economic impact on dairy. The poor efficacy of vaccines and their inability to prevent disease transmission is conducive to the use of antibiotics to control CA. However, only a few groups of antimicrobial agents are effective against these species, and selecting an adequate antimicrobial agent following the categorization of antibiotics made by the different international organisms (European Medicine Agency, World Health Organization) in veterinary medicine becomes a difficult task. The PK/PD approach is a useful tool to guide veterinarians on the appropriate targets through a rational selection of the best dose regimen of antimicrobial agents. In this study, marbofloxacin pharmacokinetics was studied after three routes of administration with two long-acting formulations. The minimum inhibitory concentrations (MIC) values of Mycoplasma agalactia isolated from goats affected by CA in Spain were calculated. The results show that systemic exposure achieved in lactating goats following these formulations provides rate of drug release that could be adequate to maintain effective plasma concentrations against M. agalactiae. The PK/PD analysis by Monte Carlo simulation showed that a dosage regimen from 8.47 to 11.57 mg/kg every 24 h could effectively treat goats affected by CA. ABSTRACT: Contagious agalactia is a mycoplasmosis affecting small ruminants that have become an important issue in many countries. However, PK/PD studies of antibiotics to treat this problem in lactating goats affected by Mycoplasma (M.) agalactiae, the main CA-causing mycoplasma are almost non-existent. The aims of this study were to evaluate the plasma and milk disposition of marbofloxacin in lactating goats after intravenous (IV), subcutaneous (SC) and subcutaneous poloxamer P407 formulations with and without carboxy-methylcellulose (SC-P407-CMC and SC-P407) administration. Marbofloxacin concentrations were analysed by the High Performance Liquid Chromatography (HPLC) method. Minimum inhibitory concentrations (MIC) of M. agalactiae field isolates from mastitic goat’s milk were used to calculate surrogate markers of efficacy. Terminal half-lives of marbofloxacin after IV, SC, SC-P407 and SC-P407-CMC administration were 7.12, 6.57, 13.92 and 12.19 h in plasma, and the half-lives of elimination of marbofloxacin in milk were 7.22, 7.16, 9.30 and 7.74 h after IV, SC, SC-P407 and SC-P407-CMC administration, respectively. Marbofloxacin penetration from the blood into the milk was extensive, with Area Under the Curve (AUC(milk)/AUC(plasma)) ratios ranged 1.04–1.23, and maximum concentrations (C(max-milk)/C(max-plasma)) ratios ranged 0.72–1.20. The PK/PD surrogate markers of efficacy fAUC24/MIC and the Monte Carlo simulation show that marbofloxacin ratio (fAUC(24)/MIC > 125) using a 90% of target attainment rate (TAR) need a dose regimen between 8.4 mg/kg (SC) and 11.57 mg/kg (P407CMC) and should be adequate to treat contagious agalactia in lactating goats.